Budgets Quality under international standards - Doaim, Sarmad Salman; Jarullah, Mahdi Abed (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the quality of budgets in light of international standards in Iraqi banks, and to achieve the objectives of the study, the researcher designed a questionnaire whose questions included various aspects related to the quality of budgets in light of international standards. The study sample consisted of (80) employees working in banks. By distributing the questionnaire to the individuals of the study sample related to preparing budgets in banks,The study concluded with the most important results of activating the planning function in Iraqi banks through appropriating budgets, and that budget approval has a fundamental role in light of international standards on monitoring and evaluation, and the study recommended that Iraqi banks adopt international standards as the basis for monitoring and evaluation of performance, and increasing the banks ’interest. And higher departments accurately predict revenues and expenditures and work to analyze them and address deviations in them.